Sarcoidose: Uma forma rara de apresentação - Cemlyn-Jones, J (2011)
The clinical presentation of sarcoidosis is diverse and in over 90% of patients there is pulmonary involvement. The most common features of the radiographic findings at the time of diagnosis are bilateral hilar lymphadenopathy and pulmonary infiltration. The authors report the case of a young female patient who presented with multiple bilateral nodular shadows on chest radiograph. Surgical biopsy revealed non-necrotizing granulomas with occasional multinucleated giant cells compatible with sarcoidosis. Although this was a case of stage III pulmonary disease, the patient was asymptomatic, lung function tests were normal and there were no signs of extrathoracic involvement. Spontaneous remission occurred without treatment as shown on high resolution CT scan follow-up, one year later.